Revisiting Labor Market Regulations in the Middle East and North Africa - Hatayama, Maho (World Bank, Washington, DC, 2022)
Labor regulations are important determinants of resource allocation, productivity, and labor market outcomes. They can protect workers’ rights, enhance job security, and improve working conditions. However, overly restrictive regulations can also increase business costs, becoming barriers to creating formal employment, particularly for vulnerable workers. This paper analyzes the key characteristics of labor market regulations in the Middle East and North Africa (MENA) and benchmarks them against international practices. The main objective is to identify strengths and weaknesses in the regulations and to inform governments about policy options to enhance employment outcomes in the region. The paper focuses on labor laws and regulations concerning hiring, working hours, minimum wage, redundancy rules and cost, unemployment insurance, labor tax and social security contributions, and legal frameworks affecting women’s work. This paper finds that the region has generally flexibly hiring rules, but that redundancy regulations are relatively rigid and costly compared to international practices. Statutory minimum wages and labor taxes are not very high, with the exception of a few countries. Although many countries have made efforts to remove legal barriers for women workers, discriminatory laws still restrict their participation in the labor market. While labor market regulations vary by country, the findings suggest areas where there is clear scope to improve the design and implementation of labor market regulations to facilitate stronger formal labor demand and to enhance efficient resource allocation; and at the same time, to strengthen compliance to provide necessary protections to workers.